Le projet de sauvegarde de la collection Bens Delicatessen. Bien plus que les archives du smoked meat! - Cartier, François (Archives, 2008)
Keywords: Archives; Confédération des syndicats nationaux; Musée McCord; Musées; Restaurant

A Heuristic Archive: Jean-Paul Gill's Red Light Photographs - Guillaume, Philippe (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Archives; Patrimoine; Photographie; Quartiers; Saint-Laurent (quartier)

Bref aperçu sur l'histoire des archives de la chancellerie de l'archevêché de Montréal - Beaudin, François (La Société canadienne d'histoire de l'Église catholique, 1964)
Keywords: Archevêché; Archives

Female Authorship, Incomplete Archives, and the Periodical Press in Nineteenth Century Montreal: The Case of Rosanna Mullins Leprohon - Cabajsky, Andrea (Port Acadie, 2022)
Keywords: Archives; Femmes; Écrivains

Historienne, mentore, libre-penseuse: réflexions autour de l'oeuvre d'Andrée Lévesque - Fahrni, Magda (Profession historienne? Femmes et pratique de l’histoire au Canada français, XIXe-XXe siècles, 2023)
Keywords: Archives; Femmes; Histoire

Des archives de femmes pour le début du siècle - Pinard, Yolande (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1976)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste; Montreal Local Council of Women

The Christian Pavilion at Expo 67: Notes from Charles Gagnon's Archive - Kin Gagnon, Monika (Expo 67: Not Just a Souvenir, 2010)
Keywords: Cinéma; Expositions

Identities, Communities, and the Infrastructures of History: Creating Canadian Jewish Archives in the 1930s and the 1970s - Menkis, Richard (History, Memory, And Jewish Identity, 2015)
Keywords: Congrès juif canadien; Histoire; Juifs

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Keywords: Danse; Femmes; Histoire; Musicien; Musique

Reading the Multimedia Archive Surrounding Montreal's Post-War LGBTQ Bars: A Genealogical Return to Madame Arthur and Il était une fois dans l'Est - Pidduck, Julianne (Quebec Studies, 2015)
Keywords: Alcool

L'école Saint-Stanislas supérieure et secondaire 1929-1977: l'esprit en mouvement de plusieurs générations - Moineau, Guy; Laprotte, Jean (Archives F.I.C., 2015)

C'était mon frère... Supplément I, 1965-1976 - Saint-Pierre, Bertrand; Poirier, Léandre (Archives des Franciscains, 1976)
Keywords: Communautés religieuses; Franciscains

Regards catholiques sur les villes québécoises: une haine à géométrie variable (1918-1939) - Bérubé, Harold (Archives de sciences sociales des religions, 2014)

Through the Lens of Edith Mather: Photographing Demolition and the Transforming City - Southcott, Tanya (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Conservation; Femmes; Patrimoine; Photographie; Rues

Re-activations: Alain Chagnon’s Plateau-Mont-Royal in Translation - Langford, Martha (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Photographie; Plateau Mont-Royal; Quartiers

Le Royal Victoria Hospital et l'instauration du régime d'assurance-maladie québécois 1965-1971 - Charpentier, Alix (Université d'Angers, 2003)
Keywords: Assurance; Hôpitaux; Royal Victoria Hospital

Le Montreal Council of Women / Conseil des Femmes de Montréal, de 1940 à 1967, à travers les questions de planification urbaine, d'immigration et des femmes dans le monde du travail - Hilairet, Sabine (Université d'Angers, 2003)
Keywords: Femmes; Féminisme; Montreal Local Council of Women; Travail

''Il y a des chose qu'une personne cultivée ne peut ignorer''- Le Bulletin de la Société d'étude et de conférences (1915-1967): sa genèse, ses actrices et son contenu. - St-Laurent, Fanie (Revue de Bibliothèque et Archives nationale du Québec, 2012)
Keywords: Femmes

Trente années d'université, 1914-1944 - Chartier, Émile (Université de Montréal, Service des archives, 1982)
Keywords: Université de Montréal

The Blessed Communion: The Origins and History of the Diocese of Montreal, 1760-1960 - Cooper, John Irwin (Archives' Committee of the Diocese of Montreal, 1960)
Keywords: Anglicans; Diocèse; Protestants

Immigrants italiens dans l'espace social et culturel montréalais. Une synthèse historique - Ramirez, Bruno (Histoires d'immigrations à Montréal, 2014)
Keywords: Italiens

Les juifs sépharades à Montréal - Cohen, Yolande (Histoires d'immigrations à Montréal, 2014)
Keywords: Juifs

Un siècle de vie yiddish à Montréal - Anctil, Pierre (Histoires d'immigrations à Montréal, 2014)
Keywords: Juifs

La communauté écossaise de Montréal. Histoire et questions identitaires - Bourbeau, Catherine (Histoires d'immigrations à Montréal, 2014)
Keywords: Écossais

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens